On identification and estimation of Heckman models. (December 2021) - Cook, Jonathan; Lee, Joon-Suk; Newberger, Noah
In this article, we present commands to enable fixing the value of the correlation between the unobservables in Heckman models. These commands can solve two practical issues. First, for situations in which a valid exclusion restriction is not available, these commands enable exploring how the results could be affected by sample-selection bias. Second, stepping through values of this correlation can verify whether the global maximum of the likelihood function has been found. We provide several commands to fit these and related models with a fixed value of the correlation between the unobservables.